REVITALIZATION OF ADAT LAW AS AN INSTRUMENT OF SOCIAL ENGINEERING IN CENTRAL SUMBA - Umbu Rauta; Ari Siswanto (Faculty of Law, Universitas Jenderal Soedirman, 2018)
This study focuses on the use of adat law as an instrument to influence the community’s behaviors in Central Sumba, particularly those concerning the performance of traditional ceremonies. Since the social cost required to perform the ceremonies could be very high and has been regarded as one of the impetus that drives poverty in the society, there was a demand to change the practice which is regarded as a reflection of wasteful lifestyle. The main issue discussed in this study is whether adat law could be used as a tool of social engineering to change the unwanted wasteful lifestyle. This study revealed that since adat norms are still strongly held in the community, adat law could be used as an instrument to change behaviors. Social engineering measures were taken by utilizing adat law to change the prodigal behavior in the form of the declaration of the Three Moral Move-ments. Keywords: adat law, Central Sumba, social engineering, traditional rites